Quality of Life among Youths having Repaired Non-syndromic Cleft Lip and Palate in Karachi - Syeda Arzoo Azeem; Syed Mahmood Haider; Zubair Ahmed Abbasi; Zafar Abbas; Hoor u lain Iqbal (KARACHI MEDICAL AND DENTAL COLLEGE, 2022)
Abstract Objective: To compare general quality of life of youths having repaired non-syndromic CLP with controls using a generic quality of life instrument, Youth Quality of Life - Research Version (YQOL-R). Methods: case control study was conducted from January, 2017 to December, 2018. Inclusion criteria was patients having repaired non syndromic Cleft Lip and Palate, age 15 to 29 years, of either gender while controls were healthy individuals of similar age. Quality of life was measured using validated YQOL-R instrument. Data of 62 cases and 107 healthy controls, consented for study was analysed using statistical software, SPSS version 20. Results:. Mean age was 22.09+5.04. Cronbach's alpha for domains of sense of self was 0.630, relationship domain (0.795), environmental domain (0.826) and general quality of life domain was 0.688 and for YQOL-R was 0.866. Significant difference was observed for self care domain (63.10 vs. 73.50; p-value = 0.001), relationship domain (79.5 vs. 83.73; p-value = 0.013), environmental domain (70.89 vs. 84.60; p-value = 0.001), general quality of life domain (79.80 vs. 86.04; p-value = 0.012) and percent score of total perceptual score between cases and controls (73.32 vs. 81.97; p-value = 0.001).   Conclusion: Compared to cases healthy controls had a better quality of life as they have significantly better results in self care, relationship, environment and general quality of life domains along with mean perceptual percentage.